2021
DOI: 10.13189/ujar.2021.090602
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Grain Legumes to Transient Water Deficit in Timor-Leste

Abstract: In Timor-Leste, it is possible to use residual soil water after rice harvest to produce grain legumes, despite the lack of supplementary irrigation. This study aimed to identify the growth of potential grain legumes adapted to transient water deficit after rice harvest. The experiment was undertaken in 2012 at the Hera Field Research of the National University of Timor Lorosa'e, representing lowland areas, and farmland in Aileu, representing highland areas. The experiment used a completely randomized design wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 22 publications
4
1
0
Order By: Relevance
“…The current study revealed no significant impact of buffalo manure and biochar on crop phenology. In general, crop phenology in the current study was consistent with a study on soybean [7], but it was earlier than another study on soybean [8].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The current study revealed no significant impact of buffalo manure and biochar on crop phenology. In general, crop phenology in the current study was consistent with a study on soybean [7], but it was earlier than another study on soybean [8].…”
Section: Discussionsupporting
confidence: 89%
“…Because of this reason, other previous studies on horticultural crops such as watermelon used a minimum level of 3 t/ha biochar to increase yield of water melon (unpublished data) to be feasible for farmers to adopt the technology. Soybean biomass production in the current study was comparable to other study on soybean [7], but the rate of increase (7.51%) with 3 t/ha biochar (Table 1 & Figure 4B) was less than a greenhouse study [22]. The seed yield in the current study was over 100% higher with 10 t/ha buffalo manure (Table 1 & Figure 4C) and 36% higher with 3 t/ha biochar (Table 1 & Figure 4D) compared to soybean yield in a study carried out on the northeast coast of Timor-Leste with irrigation supplement [8], but the yield was comparable to another study on soybean [7].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations